[PP.24.08] RELATION BETWEEN LEFT VENTRICULAR DIASTOLIC FUNCTION PARAMETERS AND THE GRADE OF VENTRICULAR REMODELING IN A HYPERTENSIVE POPULATION. (September 2017) - Dal Canto, E.; Lenzi, V.; Forestieri, M.; Buralli, S.; Bruno, R.M.; Faconti, L.; Ghiadoni, L.; Taddei, S.
Abstract : Objective: Left ventricular hypertrophy (LVH) in hypertensive patients represents an adaptive change to the chronic exposure to elevated blood pressure (BP) values and it is a well documented risk factor for cardiovascular (CV) events. In addition to structural changes, hypertension (HT) is also responsible for functional cardiac alterations, particularly on left ventricular (LV) diastolic function (DF). Aim of the present study was to establish the relation between DF indices and LVH in a hypertensive patients free from CV disease. Design and method: 111 subjects (age 60 ± 13 years, female 32%), baseline BP 141/80 mmHg, 87.4% under pharmacological treatment, 18, 8% with type 2 diabetes (T2DM) undertook a trans-thoracic cardiac ultrasound to assess LV mass index (LVMi), relative wall thickness (RWT) and DF parameters (peak early filling - E wave - and late diastolic filling – A wave - velocities, the E/A ratio, tissue doppler anular early diastolic velocity - e'm - and E/e'm ratio) and left atrial volume index (LAVi), calculated with the biplane area-length method. Results: In the overall population LVMi was 124, 1 ± 23, 2 g/m 2, mean E/A was 0, 95 ± 0, 35, E/e'm 8, 92 ± 3, 07 and LAVi 30, 6 ± 13, 2 ml/m 2 . At the univariate linear regression analysis LAVi, E/A and E/E'm showed significant correlation with LVMi (p < 0.001, R = 0.42; p < 0.001, R = −0.43; p < 0.001, R = 0.58 respectively) and with RWT (p < 0.001, R = −0.44; p < 0.005, R = −0.25; p < 0.005, R = 0.27 respectively). However, at the multiple regression analysis, only E/E'm and LAVi were statistically significantly associated with LVMi, indipendently of confounders (age, BP, T2DM). Conclusions: Although age, BP and T2DM constitute the main determinants of DF, E/e'm and LAVi have an indipendent significant correlation with LVMi, confirming the tight relation between hypertension and diastolic dysfunction in the presence of LVH.